O Point-And-Click adventure ressurge: uma discussão analítica sobre um gênero adormecido - Vasconcellos, Nícolas Souza de Frias e (2020)
In the mid-1980s, a genre would revolutionize the gaming market for personal computers and the gaming industry. The type of point-and-click adventure game that emerged with the evolution of a game genre born in the 1960s: text based adventure game, would become a graphic based adventure game and later evolve into the so-called genre that is studied in this research: point-and-click adventure. Thus, this work aims to carry out the analysis of this genre of digital game from its evolution in time, which goes from its creation, passing through all its development and ending in its consolidation in the 1980s and early 1990s. In the following years, there was a weakening of this type of digital game that almost disappeared from the market, reaching, finally, a rebirth in the North American market through the company Double Fine, with the release of the game Broken Age (2015) in a resounding campaign carried out on Kickstarter (the largest financing site for innovative products in the world). The revival of this genre produced a documentary entitled Double Fine Adventure (2016) that is used as supporting material in this research, produced by 2 Player Productions and Double Fine Productions. Therefore, initially, this work aims to serve as a basis for historical study on the development and dissemination of a genre of games that was considered abandoned or at least in a state of dormancy. In fact, this research focuses on the description and classification of the fundamental characteristics and mechanics for understanding the concepts that involve point-and-click adventure games. Here, a case study of the game Broken Age (2015) was carried out as well, observing and highlighting the mechanics and characteristics proposed by this game genre, which was adapted to the contemporary digital games market. Therefore, this work proposes a discussion about the possible reasons that led the games of the pointand- click adventure genre to reappear in the American market, considering that it never completely disappeared from the market across the world, mainly in the European market. Finally, an analysis of point-and-click adventure games is proposed, based on bibliographic studies and on renowned authors such as: Katie Zalem, Jesse Schell, among others as well